The comparison of sport interests in metropolitan and small town elementary school boys - Bosnar, Ksenija (Array, 2004)
The aim of this work is to establish the differences of sport preferences in elementary school pupils from small town with modest sport infrastructure, and big town with number of sport facilities. The subjects were male elementary school pupils aged 11-15 years from small town in continental part of the country, and from hundred times more inhabited capital. Total number of both samples is 1072 boys. The subjects were given the list of 52 sports to be evaluated on five-point scale ranging from particularly unattractive sport to activity particularly attractive to examinee. The results show that the rank of the most popular as well as least popular sports is the same in both samples. However, discriminant analysis shows that differences do exist. The discriminant function is defined mainly by baseball, skating and scuba diving at the negative pole, and by bowls and box at the positive side. Small town boys are more ready to accept non-elite bowls and box, while metropolitan boys more often prefer typically urban skating, rather new baseball, and fashionable scuba diving. It could be concluded that differences in metropolitan and small town way of life reflect in sport preferences in elementary school boys.